MANAGEMENT OF TEACHING PERSONNEL IN IMPROVING THE QUALITY OF EDUCATION: A CASE STUDY AT MUHAMMADIYAH 1 BESUKI INTEGRATED ELEMENTARY SCHOOL - Shoofiya, Gheitsaa’ Zaahira; yamin, idris; Baharun, Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Educator management is a process of planning, organizing, directing, coordinating, supervising, and controlling teaching staff within an organizational scope—educator management participates in all educational processes as educators with their respective duties. Muhammadiyah 1 Besuki Integrated Primary School is one of the superior educational institutions, and one of the supporting factors of its excellence is the management of its educators. All processes in the teaching staff management must have a clear, precise, and firm division of responsibilities so that the program that has been set can run well and that all educators want to work to carry out the tasks given. This study aims to describe How the integration between recruitment, selection, and placement of learner responsibilities can support the optimization of educators' workload to improve the quality and quality of education at the integrated elementary school of Muhammadiyah 1 Besuki. This research uses a qualitative approach and conducts research using descriptive methods.